The different causes of brachial plexus injuries - Hasan, Syed Asif; Aljammaz, Abdulrahman Saad; AlGhamdi, Mosleh Motesh; ALQattan, Mohamed Jasim; Alsalman, Abdulrahman Hussain; Alhifzi, Wafaa Sulaiman; Aljudia, Hassan Ahmed; Alqahtani, Mazen Jarallah; Ali, Abdullrahman Mohammed; Almutairi, Ahad Mohammed; Bukhamseen, Abrar Hasan (International Journal Of Community Medicine And Public Health, 2021)
Many etiologies have been reported to account for injuries to the brachial plexus, peripheral nerves and trauma. Additionally, many diseases have also been reported to cause the injury with many different pathophysiologies. For instance, some diseases have been classified as the primary diseases of the peripheral nerves including hereditary neuropathy. In the same context, brachial plexus damage or injury might also result secondary to a systemic disease, leading to a significant peripheral nerve injury as in cases with most metabolic neuropathies, which may result secondary to renal insufficiency, diabetes, amyloidosis and many other diseases. Furthermore, toxic and iatrogenic causes were also reported as potential causes for brachial plexus injuries. However, traumatic events are the most commonly reported, owing to motorcycle accidents, being the most common etiology. Although evidence is now abundant regarding the etiology, further studies are needed to furtherly validate the evidence and for more specification of the etiology and the underlying mechanisms.